Chemical biology of mutagenesis and DNA repair: cellular responses to DNA alkylation - Shrivastav, Nidhi (Oxford University Press, 2010)
The reaction of DNA-damaging agents with the genome results in a plethora of lesions, commonly referred to as adducts. Adducts may cause DNA to mutate, they may represent the chemical precursors of lethal events and they can disrupt expression of genes. Determination of which adduct is responsible for each of these biological endpoints is difficult, but this task has been accomplished for some carcinogenic DNA-damaging agents. Here, we describe the respective contributions of specific DNA lesions to the biological effects of low molecular weight alkylating agents.